2012
DOI: 10.1093/cercor/bhs248
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging on Properties of the Local Circuit in Rat Primary Somatosensory Cortex (S1) In Vitro

Abstract: During aging receptive field properties degrade, the ability of the circuit to process temporal information is impaired and behaviors mediated by the circuit can become impaired. These changes are mediated by changes in the properties of neural circuits, particularly the balance of excitation and inhibition, the intrinsic properties of neurons, and the anatomy of connections in the circuit. In this study, properties of thalamorecipient pyramidal neurons in layer 3 were examined in the hindpaw region of rat pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 65 publications
4
29
0
Order By: Relevance
“…Furthermore, in-vitro studies showed that both excitation and inhibition were affected during aging43. Based on these findings, and the enhanced activation in SI (see Fig.…”
Section: Resultsmentioning
confidence: 68%
“…Furthermore, in-vitro studies showed that both excitation and inhibition were affected during aging43. Based on these findings, and the enhanced activation in SI (see Fig.…”
Section: Resultsmentioning
confidence: 68%
“…A consistent finding across the sensory cortex is a decline in inhibitory neurotransmission with age (Leventhal et al, 2003; Caspary et al, 2008; Syka, 2010; Hickmott and Dinse, 2013). Processing of rapidly changing spectrotemporal cues, such as those present in speech, depends on interactions between excitatory and inhibitory components of the auditory neuron receptive field (Zhang et al, 2003; Razak and Fuzessery, 2006, 2008, 2009; Sadagopan and Wang, 2010; Trujillo et al, 2013).…”
Section: Introductionmentioning
confidence: 87%
“…AP threshold is the critical level to which the membrane potential must be depolarized in order to initiate an AP and hence it is often used as a measure for neuron excitability. Recent studies have reported an age-related increase in the AP threshold of the rat hippocampal CA1 pyramidal cell (HP-CA1-PC; Matthews et al, 2009 ) and primary somatosensory cortex layer 3 pyramidal cell (S1-PC) (Hickmott and Dinse, 2013 ), mice (Randall et al, 2012 ) and rabbit HP-CA1-PC (Power et al, 2002 ) and also in the ventral pleural ganglion sensory neuron (PVC-SN) and buccal ganglion sensory neuron (BSC-SN) of aging Aplysia (Kempsell and Fieber, 2014 ). While the basis of this change has not yet been clarified, age-related depolarization of the AP threshold could likely be ascribed to alterations of voltage-gated Na + channel (Na v channel) activation properties or channel subtype expression patterns (Randall et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%